Regional isolation in the right atrium with disruption of intra‐atrial conduction after catheter ablation of atrial tachycardia. (9th July 2019) - Markowitz, Steven M.; Choi, Daniel Y.; Daian, Foysal; Liu, Christopher F.; Cheung, Jim W.; Thomas, George; Ip, James E.; Lerman, Bruce B.
Abstract: Background: Ablation of atrial tachycardia (AT) that occurs after cardiac surgery or prior ablation often requires complex lesion sets. In combination with the pre‐existing atrial scar, these lesion sets may result in inadvertent intra‐atrial conduction block. This study reports the phenomenon of incidental isolation of right atrial (RA) regions that occurs secondary to AT ablation, which in some cases results in profound bradycardia due to sinus exit block. Methods and Results: Intracardiac electrograms were examined in consecutive patients who underwent AT ablation in the RA. Cases of localized isolation of the RA were defined as areas that developed electrical dissociation during ablation. Of 132 patients having ablation in both the RA free wall and the cavotricuspid isthmus (CTI), 10 (7.6%) developed unintentional isolation of the lateral RA. Five of these patients had prior mitral valve surgery, comprising 12.2% of all 41 patients with mitral surgery who underwent ablation in the CTI and the RA free wall. All patients with regional isolation had a pre‐existing scar in the lateral wall of the RA. In six patients, isolation of the lateral RA resulted in profound bradycardia due to exit block from the peri‐sinus node myocardium. Conclusions: Complex ablation lesions in patients with prior valve surgery, prior ablation, or atrial myopathy may result in unintended localized conduction block in the RA. In some cases, isolation of the lateral RA can result in complete sinus exit block with profound bradycardia requiring pacemaker implantation.